EVALUASI KEMAMPUAN MEMBACA AL-QUR’AN BERDASARKAN MAKHARIJUL HURUF DAN PENERAPAN TAJWID DI MUSHOLA BAITUL IZZAH - Devi Fatimatuz Zahro; Hanif Raharjo; Agung Setia Budi; Marjen Mingguwanto; Satria Wiharyanto Dwi Putra; Moh. Maulidan Sudito; Zaenul Fuad; Ahmad Sifaul Fikri; M. Rohidin (STKIP Subang, 2026)
A The ability to read the Quran correctly is the responsibility of every Muslim. However, many children at the Baitul Izzah prayer room (Mushola Baitul Izzah) still lack a complete understanding of the pronunciation of letters and the application of Tajweed, which can affect the accuracy and beauty of their recitation. Therefore, an evaluation of the quality of Quran recitation at the prayer room is necessary as part of the learning improvement process.